ASSESS_TTIP: Assessing the claimed benefits of the Transatlantic Trade and Investment Partnership (TTIP) - Werner G. Raza; Jan Grumiller; Lance Taylor; Bernhard Tröster; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2014)
What are the economic effects of TTIP? In the public debate, a few selected studies, mostly commissioned by the European Commission, have set the tone, suggesting that effects are positive on both sides of the Atlantic. The studies are from Ecorys (2009), CEPR (2013), CEPII (2013) and Bertelsmann/ifo (2013). In this review, we critically assess these findings and their underlying methodologies. In addition, we discuss some issues, which are frequently neglected by trade impact assessments, but are nevertheless important from our point of view. In a nutshell, we see limited economic gains, but considerable downside risks.
Keywords: 330